The acute effects of knee extension exercises with different contraction durations on the subsequent maximal knee extension torque among athletes with different strength levels - Nakata, K.; Mishima, T. (PLOS ONE, 2022)
Individuals with high fatigue resistance against a high-intensity conditioning activity (CA) may be able to avoid experiencing significant fatigue and enhance their voluntary performance. We examined whether the optimal contraction duration of dynamic knee extension exercises to maximize subsequent voluntary performance varies depending on the strength level of an individual. The study participants were 22 male American college football players. Initially, all participants performed a 10-s maximal isometric knee extension exercise and were classified as stronger individuals (n = 8) and weaker individuals (n = 8) based on their relative muscle strength. Each group then performed three types of dynamic CA with different contraction durations (6 s [6-CA], 12 s [12-CA], and 18 s [18-CA]) in random order. To observe the time-course changes in post-activation potentiation and performance enhancement, the twitch torques induced by electrical stimulation and isokinetic knee extension torques at 180°/s were recorded before and after each CA. The twitch torque increased at 10 s (29.5% ± 9.3%) and 1 min (18.5% ± 6.8%) after 6-CA for the stronger individuals (p < 0.05). However, no post-activation potentiation was induced in the weaker individuals in either protocol. Voluntary performance increased at 4 (7.0% ± 4.5%) and 7 (8.2% ± 4.3%) min after 18-CA for stronger individuals (p < 0.05). However, there was no post-activation performance enhancement in either protocol for weaker individuals. Thus, CA with a relatively long contraction duration was optimal to maximize the subsequent voluntary performance for stronger individuals. It remains unknown whether CAs performed with relatively short or long contraction durations were optimal for weaker individuals.